An Anthracene‐Based Metal‐Organic Framework for Selective Photo‐Reduction of Carbon Dioxide to Formic Acid Coupled with Water Oxidation. Issue 12 (31st January 2021) - SK, Mostakim; Barman, Soumitra; Paul, Shounik; De, Ratnadip; Sreejith, S. S.; Reinsch, Helge; Grzywa, Maciej; Stock, Norbert; Volkmer, Dirk; Biswas, Shyam; Roy, Soumyajit
Abstract: A Zr‐based metal‐organic framework has been synthesized and employed as a catalyst for photochemical carbon dioxide reduction coupled with water oxidation. The catalyst shows significant carbon dioxide reduction property with concomitant water oxidation. The catalyst has broad visible light as well as UV light absorption property, which is further confirmed from electronic absorption spectroscopy. Formic acid was the only reduced product from carbon dioxide with a turn‐over frequency (TOF) of 0.69 h −1 in addition to oxygen, which was produced with a TOF of 0.54 h −1 . No external photosensitizer is used and the ligand itself acts as the light harvester. The efficient and selective photochemical carbon dioxide reduction to formic acid with concomitant water oxidation using Zr‐based MOF as catalyst is thus demonstrated here. Abstract : A Zr‐based photoactive metal‐organic framework was synthesized under solvothermal condition. It could reduce the carbon dioxide coupled with water oxidation under UV/Visible light. Also, it selectively reduced the carbon dioxide than the free ligand with a turn‐over frequency (TOF) of 0.69 h −1 for formic acid and produced oxygen with a TOF of 0.54 h −1 .